2019
DOI: 10.5897/jpbcs2018.0800
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic variability, heritability, genetic advance and correlation for agronomic and yield components in common bean landraces from South western Kenya

Abstract: The present study was conducted to estimate the genetic variability, heritability, genetic advance and association among selected agronomic traits of common bean landraces from South western Kenya. The field experiment was conducted using 52 common bean landraces at the Kenya Agricultural and Livestock Research Organization (KALRO), Kisii Research Center during 2015 and 2016 main cropping seasons. The experimental design was randomized complete block (RCBD) with three replications. Analysis of variance reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
0
0
Order By: Relevance
“…Seed weight was the trait that showed the greatest estimate of heritability (h 2 , 91.4%) in the present study. This was expected, as the literature is full of studies that have reported such observations for common bean [54][55][56]. This outcome is also consistent with what has been shown for other legume crops, such as chickpea [57,58], lentil [59], faba bean [60], soybean [61] and pea [62].…”
Section: Morphological Seed Traitssupporting
confidence: 88%
“…Seed weight was the trait that showed the greatest estimate of heritability (h 2 , 91.4%) in the present study. This was expected, as the literature is full of studies that have reported such observations for common bean [54][55][56]. This outcome is also consistent with what has been shown for other legume crops, such as chickpea [57,58], lentil [59], faba bean [60], soybean [61] and pea [62].…”
Section: Morphological Seed Traitssupporting
confidence: 88%
“…The phenotypic coefficient of variation was of a high significance than the genotypic coefficient of variation for all the traits suggesting the environmental effect in the expression of those parameters. A similar result was reported on evaluation of genetic variability, heritability, genetic advance and correlation for agronomic and yield components in common bean landraces from South western Kenya by Anunda [49] and assessment genotypes of groundnut for pod yield and its component traits for pod yield and its component traits by Kavitha, [50]. and eminence apparatuses under organic and conservative fertilizer managements in organic and conformist nourishment managements in groundnut by Bhargavi, [51].…”
Section: Genetic Variabilitysupporting
confidence: 77%
“…branches per plant. The last three parameters followed Esther and Adomako (2010). Coffee trees to be used for root: shoot ratios determination was taken through the excavation method where all the roots were dug and removed from the soil.…”
Section: Growth Characteristicsmentioning
confidence: 99%